2017
DOI: 10.3389/fpsyg.2017.00334
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction between Central and Peripheral Processing in Chinese Handwritten Production: Evidence from the Effect of Lexicality and Radical Complexity

Abstract: The interaction between central and peripheral processing in written word production remains controversial. This study aims to investigate whether the effects of radical complexity and lexicality in central processing cascade into peripheral processing in Chinese written word production. The participants were asked to write characters and non-characters (lexicality) with different radical complexity (few- and many-strokes). The findings indicated that regardless of the lexicality, the writing latencies were lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 50 publications
9
23
0
Order By: Relevance
“…No differences in latency between conditions were detected [ F (2, 91) = 0.6, p = 0.551]. Moreover, correlation analysis demonstrated that writing duration and latency were significantly correlated for high frequency characters ( r = −0.34, p = 0.029), low frequency characters ( r = −0.53, p = 0.002), and geometric symbols ( r = −0.38, p = 0.034), consistent with the interaction viewpoint between central and peripheral processes during writing (Roux et al, 2013 ; Kandel and Perret, 2015 ; Zhang and Feng, 2017 ).…”
Section: Resultssupporting
confidence: 69%
“…No differences in latency between conditions were detected [ F (2, 91) = 0.6, p = 0.551]. Moreover, correlation analysis demonstrated that writing duration and latency were significantly correlated for high frequency characters ( r = −0.34, p = 0.029), low frequency characters ( r = −0.53, p = 0.002), and geometric symbols ( r = −0.38, p = 0.034), consistent with the interaction viewpoint between central and peripheral processes during writing (Roux et al, 2013 ; Kandel and Perret, 2015 ; Zhang and Feng, 2017 ).…”
Section: Resultssupporting
confidence: 69%
“…It is widely agreed that increased written latencies reflect increased demands at the central levels of processing (Afonso & Álvarez, 2011;Delattre, Bonin, & Barry, 2006;Zhang & Feng, 2017). Thus, the pattern of results reported here may be consistent with an evolution of the writing difficulties from the most central level of processing (which it would be already affected in MCI) that would progress to affect lower levels of processing in mild AD.…”
Section: Discussionsupporting
confidence: 83%
“…More recently, Q. Zhang and Feng (2017) investigated whether effects on the central processes of handwriting spill over to the actual handwriting. They found that both lexicality (whether or not an experimental stimulus was a character) and radical complexity (number of strokes) affected the actual execution of handwriting.…”
Section: Central and Peripheral Processes In Handwritingmentioning
confidence: 99%
“…The number of stokes and the number of radicals have also been shown to be important determinants in Chinese character naming (Leck, Weekes, & Chen, 1995;Leong, Cheng, & Mulcahy, 1987;Peng & Wang, 1997;Zhou, Shu, Bi, & Shi, 1999) and to affect handwriting (Q. Zhang & Feng, 2017). In addition, to write a Chinese character, one needs to arrange the radicals in a particular spatial composition (and in a particular temporal order).…”
mentioning
confidence: 99%